Gambaran Tingkat Pengetahuan Dan Ph Rongga Mulut Terhadap Jumlah Karies Gigi M1 Permanen Pada Anak Usia 9-12 Tahun Di Mi Syafaat Muhammadiyah Jetis Kecamatan Baki Kabupaten Sukoharjo - Anggoro, Deni Argo; , drg. Ana Riolina, MPH; , drg.Retno Sari (2016)
Children in the elementary school who had good oral hygiene, ussually had neutral pH of saliva. Oral health could be realized if the salivary pH neutral. Saliva with pH neutral, made the number of plaque and low caries was not easily formed. Such conditions as the initial trigger for the establishment of oral health was good. The good and healthy food selection with health behaviours that made neutral saliva's pH. The purpose of this study was to descided the level of knowledge, saliva's pH of the oral cavity on first permanent molar dental caries in children aged 9-12 years in MI Syafaat Muhammadiyah desa Jetis kecamatan Baki kabupaten Sukoharjo. The sample as much as 72 samples and total sampling. This type of research was descriptive used cross sectional. Data were obtained from uestionnaire, saliva's pH inspectioned add the first permanent molar caries inspection in children age 9-12 years old. Based on the inspection 72 samples were obtained the result of caries are 3 children (4.2%) was high caries, 11 children (15.3%)was moderate caries, 17 children (23.6%) was low caries and 38 children (52.8%) was very low caries.